Contribution of avoidable causes of death to premature mortality in Poland and selected European countries - Wojtyniak, Bogdan; Stokwiszewski, Jakub (Studia Demograficzne, 2020)
Our study, availing the new, agreed by the OECD and Eurostat, lists of preventable and treatable causes of death, seeks to quantify the contribution of avoidable causes to premature mortality and its dynamics in Poland and Central European countries – Czechia, Hungary, Lithuania and Slovenia, in comparison with Sweden serving as a benchmark country in 1999–2017. We calculated age standardised death rates for the broad groups of avoidable causes and more specific ones, which comprised preventable and treatable cancer and diseases of the circulatory system (DCS), preventable injuries and alcohol-related diseases. Deaths from not avoidable causes were also analysed. The analysis of time trends in the death rates and calculation of the Average Annual Percent Change (AAPC) for the overall trend were performed with joint-point models. The contribution of changes in mortality from avoidable causes to increase life expectancy during 1999–2017 and contribution of the difference in mortality from these causes to the difference in life expectancy between five countries and Sweden were based on the decomposition of temporary life expectancy between birth and age 75 [e(0-75)]. For the calculation of life expectancy, we used the classic Chiang method and the decomposition of life expectancy by the death causes and age was conducted with the Arriaga method. The AAPC of death rates from avoidable causes in 1999–2017 was similar in all the countries but Lithuania, where the decline started later. The decline in the death rates from not avoidable causes is much slower than the rates from avoidable causes. Mortality from treatable causes was decreasing faster than from preventable causes in most populations. In 1999–2017, the average rate of mortality decline for preventable cancer was greater among men than among women, while for treatable cancer the sex-related differences were much smaller and in favour of women. As for preventable and treatable death from DCS, their decrease was faster among women than men in all the countries but Sweden. Improvements in mortality from causes that could be avoided through prevention or treatment made substantial positive contributions to the overall change in life expectancy in all the countries. The differences in temporary life expectancy e(0-75) between the analysed Central European countries and Sweden were much smaller in 2017 than in 1999, due to the reduction of the gap in mortality from avoidable causes. Our results show that among men, and to a lesser extent among women, mortality from preventable causes contributes more than mortality from causes that can be effectively treated to shorter life expectancy in the countries of Central Europe than in Sweden. This indicates that in reducing the health gap between the inhabitants of Central Europe and Western Europe, the healthcare system should consider disease prevention even to a greater extent than just treating them.